Gallstone disease and metabolic syndrome: before and after the cholecystectomy - Yu. P. Uspensky; S. V. Ivanov; A. V. Vovk; A. V. Koscheev; Kh. I. Ganbarova (Лечащий Врач, 2021)
The review article presents the main aspects of the pathogenic relationship between gallstone disease and metabolic syndrome, and the results of studies confirming its clinical significance. The article focuses on the loss of gallbladder function as a result of cholecystectomy and the metabolic consequences of this surgical intervention.